Emilio Prados y la ausencia iluminante de lo real maravilloso - Lacalle Ciordia, Mª Ángeles (Huarte de San Juan. Filología y Didáctica de la Lengua, 2003)
Prados tries to recover the illuminated substance which is continously renewing itself of which he had got a momentary glimpse of and which spurs him on. This desire makes him to explore the night which holds the unity of the double image: the read ono and the reflected one. Through the love and the death he will obtain signals or reflections of this speculative substance of his transcendental being.